Enhanced thermoelectric performance and tunable polarity in 2D Cu2S-phenol superlattices composites for solar energy conversion. (June 2021) - Li, Kuncai; Xu, Liqing; Li, Zhanchao; Wang, Yizhuo; Wang, Jing; Qi, Xia; Li, Qing; Wang, Hong
Abstract: Solar energy conversion is of great interest in developing green and sustainable energy. Herein, we report the solar-to-electricity capability of a new two dimensional (2D) Cu2 S-phenol superlattice (CP-SL) and carbon nanotubes (CNTs) composites for the first time. CP-SL is demonstrated to have a high Seebeck coefficient and a low thermal conductivity comparable to that of metal-organic frameworks. CP-SL based solar thermoelectric generator (STEG) exhibits stable output voltages for long time usages superior to previously reported STEGs. The device is made of p- and n-type modules that are composed of CP-SL/CNT and CP-SL/polyethyleneimine (PEI) doped CNTs (PEI-CNT) composites, respectively. The polarity of the composites is dominated by the CNTs which have higher carrier concentration. The carrier transport mechanism in the composites matches well with a parallel model, indicating the CP-SL and CNT interfaces play a minor role in carrier transport. The maximum ZT value of CP-SL/CNT is achieved by an in-situ growth method, which is about 35 times higher than that of the original CP-SL. These results indicate that 2D CP-SL is a new material with tunable thermoelectric properties and polarities, which may lay a foundation to realize p- and n-type properties in one material for single-material organic electronic devices development. Graphical Abstract: ga1 Highlights: New organic superlattices with large Seebeck coefficient and low thermal conductivity, comparable to MOFs. Methodology of obtaining high electrical conductivity without significantly increasing thermal conductivity. Extensive experimental studies to unveil the origin of mixed carrier in composites, promising for single-material devices.